Enterococcal PrgU Provides Additional Regulation of Pheromone-Inducible Conjugative Plasmids - Lassinantti, Lena (mSphere, 2021)
Efficient horizontal gene transfer of the conjugative plasmid pCF10 from Enterococcus faecalis depends on the expression of its type 4 secretion system (T4SS) genes, controlled by the P(Q) promoter. Transcription from the P(Q) promoter is tightly regulated, partially to limit cell toxicity caused by overproduction of PrgB, a T4SS adhesin. PrgU plays an important role in regulating this toxicity by decreasing PrgB levels. PrgU has an RNA-binding fold, prompting us to test whether PrgU exerts its regulatory control through binding of prgQ transcripts. We used a combination of in vivo methods to quantify PrgU effects on prgQ transcripts at both single-cell and population levels. PrgU function requires a specific RNA sequence within an intergenic region (IGR) about 400 bp downstream of P(Q). PrgU interaction with the IGR reduces levels of downstream transcripts. Single-cell expression analysis showed that cells expressing prgU decreased transcript levels more rapidly than isogenic prgU-minus cells. PrgU bound RNA in vitro without sequence specificity, suggesting that PrgU requires a specific RNA structure or one or more host factors for selective binding in vivo. PrgU binding to its IGR target might recruit RNase(s) for targeted degradation of downstream transcripts or reduce elongation of nascent transcripts beyond the IGR. IMPORTANCE Bacteria utilize type 4 secretion systems (T4SS) to efficiently transfer DNA between donor and recipient cells, thereby spreading genes encoding antibiotic resistance as well as various virulence factors. Regulation of expression of the T4SS proteins and surface adhesins in Gram-positive bacteria is crucial, as some of these are highly toxic to the cell. The significance of our research lies in identifying the novel mechanism by which PrgU performs its delicate fine-tuning of the expression levels. As prgU orthologs are present in various conjugative plasmids and transposons, our results are likely relevant to understanding of diverse clinically important transfer systems.